Dense PVDF-type polymer-in-ceramic electrolytes for solid state lithium batteries. Issue 38 (11th June 2020) - Wu, Jiajie; Wu, Xiaomeng; Wang, Wenli; Wang, Qian; Zhou, Xiaoyu; Liu, Yang; Guo, Bingkun
Abstract : Li7 La3 Zr1.4 Ta0.6 O12 (LLZTO) and polyvinylidene fluoride (PVDF) composite electrolytes (LPCEs) with a high ceramic content up to 80 wt% have been developed. Abstract : Li7 La3 Zr1.4 Ta0.6 O12 (LLZTO) and polyvinylidene fluoride (PVDF) composite electrolytes (LPCEs) with a high ceramic content up to 80 wt% have been developed. Hot pressing can significantly reduce the porosity of LPCEs and increase the conductivity to 1.08 × 10 −4 S cm −1 at 60 °C, then the LPCEs can sustain Li plating/stripping cycling for over 1500 h, and make LiFePO4 /LPCE/Li cell display a capacity retention of 86% in 200 cycles.